2008
DOI: 10.1038/sj.mt.6300306
|View full text |Cite
|
Sign up to set email alerts
|

Fully Detargeted Polyethylene Glycol-coated Adenovirus Vectors Are Potent Genetic Vaccines and Escape from Pre-existing Anti-adenovirus Antibodies

Abstract: Genetic vaccination with adenoviral (Ad) gene transfer vectors requires transduction of professional antigen-presenting cells. However, because the natural Ad receptors are expressed on many cell types, the Ad vectors currently in use are characterized by high promiscuity. In fact, the majority of injected Ad vector particles are likely to transduce non-target cells. We have analyzed various sizes of polyethylene glycol (PEG) molecules for vector particle detargeting, and our data provide evidence that the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 34 publications
5
98
0
Order By: Relevance
“…24,26,28 However, our data suggest that 20K-PEGylated Ad5, which showed the greatest reduction in immune responses and achieved the lowest level of cell association, in combination with compstatin, could represent a feasible avenue for further development of systemic adenoviral therapy. We want to emphasize that this study has again revealed the importance of using relevant models when studying immune responses against adenoviral vectors intended for use in humans.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…24,26,28 However, our data suggest that 20K-PEGylated Ad5, which showed the greatest reduction in immune responses and achieved the lowest level of cell association, in combination with compstatin, could represent a feasible avenue for further development of systemic adenoviral therapy. We want to emphasize that this study has again revealed the importance of using relevant models when studying immune responses against adenoviral vectors intended for use in humans.…”
Section: Discussionmentioning
confidence: 81%
“…This is in contrast to what has been observed in mice where PEGylation had considerable capacity to reduce immune responses and to enhance transgene expression. [24][25][26]28 We observed that the donors' ability to neutralize Ad5 had a considerable impact on the immune response both for unmodified and PEGylated Ad5. Interestingly, the presence of NAbs in plasma did not directly correlate with the neutralizing ability in whole blood, indicating that other mechanisms may be involved as well or that non-neutralizing antibodies, as determined in plasma samples, may be neutralizing in whole blood.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations